2010
DOI: 10.1038/labinvest.2010.86
|View full text |Cite
|
Sign up to set email alerts
|

Modified multipotent stromal cells with epidermal growth factor restore vasculogenesis and blood flow in ischemic hind-limb of type II diabetic mice

Abstract: Diabetes is increasing in the world and causes severe cardiovascular complications. Diabetes-induced limb ischemia leads to foot amputation and therapeutic remedies are urgently needed. Here we report that local injection of mesenchymal stem cells (MSCs) prestimulated with epidermal growth factor (EGF) restored blood flow and vasculogenesis in the ischemic hind-limb of type II diabetic (db−/db−) mice. Bone marrow cells from db−/db− mice are altered as evidenced by increased oxidative stress and reduced Akt and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 38 publications
(39 reference statements)
2
70
0
Order By: Relevance
“…Yet, the cell implantation failed to reduce cardiac fibrosis or achieve reverse remodeling in this study. Further studies in large animals to explore the methods to enhance or modify MSC function, such as gene transfer 11 and pharmacological preconditioning, 31 will be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the cell implantation failed to reduce cardiac fibrosis or achieve reverse remodeling in this study. Further studies in large animals to explore the methods to enhance or modify MSC function, such as gene transfer 11 and pharmacological preconditioning, 31 will be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…After 1 h incubation, the PA rings were frozen in liquid nitrogen. The cGMP measurements were performed using an enzyme-linked immunosorbent assay kit from Cayman Chemical (Ann Arbor, MI) according to the manufacturer's protocol and as previously described (1,6).…”
Section: Methodsmentioning
confidence: 99%
“…Xu and coworkers (2009) demonstrated that injection of BMSC treated with pancreatic extract into streptozotocinindu ced DM rats not only normalized plasma glucose and pre vented apoptosis of islet cells, but also elevated produc tion of VEGF, IGF-1 and basic fibroblast growth factor (bFGF), all of which are known to have antiapoptotic and angiogenic effects [66] . A recent in vivo study in type 2 DM (db -/db -) mice with ischemic hind limbs showed that injection of epidermal growth factor (EGF)treated BMSC into the affected hind limbs increased angiogene sis by over 90% [67] . Such angiogenesis was due to the fact that the injected BMSC differentiated into new mi crovessels (neovascularization), using intercellular adhe sion molecule1 and vascular cell adhesion protein1 for adhesion and migration [67] .Overall, it is possible that anti diabetic agents with angiogenic activity could be used to enhance blood flow to fracture sites, which may in turn accelerate bone healing, and might also prevent osteo penia/osteoporosis.…”
Section: Dm-induced Osteoporosismentioning
confidence: 99%
“…A recent in vivo study in type 2 DM (db -/db -) mice with ischemic hind limbs showed that injection of epidermal growth factor (EGF)treated BMSC into the affected hind limbs increased angiogene sis by over 90% [67] . Such angiogenesis was due to the fact that the injected BMSC differentiated into new mi crovessels (neovascularization), using intercellular adhe sion molecule1 and vascular cell adhesion protein1 for adhesion and migration [67] .Overall, it is possible that anti diabetic agents with angiogenic activity could be used to enhance blood flow to fracture sites, which may in turn accelerate bone healing, and might also prevent osteo penia/osteoporosis. Conversely, certain rheological drugs, such as pentoxifylline, which increase blood flow and osteoblast activity, might be promising as antiosteoporotic agents in both DM and nonDM patients [68] .…”
Section: Dm-induced Osteoporosismentioning
confidence: 99%